Pengetahuan tentang Covid-19 pada Remaja Santri PAYD Muhammadiyah Gombong - Podo Yuwono; Fajar Agung Nugroho; E Ernawati; Dadi Santoso (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
The emergence of COVID-19 pandemic is one of the major concerns among pesantren. PAYD (The Orphanage and the poor) Muhammadiyah Gombong is an orphanage with a semi-pesantren system that focuses on memorizing the Qur'an. Lack of socialization in efforts to prevent COVID transmission from health workers among Islamic boarding schools of PAYD. Objective: Finding out the level of knowledge about COVID-19 in adolescent students in PAYD Muhammadiyah Gombong. Method: The lecture and discussion method used by prioritizing the Student Learning Center. A total of 29 (twenty-nine) male students participated as respondents (total sampling). With the pre-post and post-test, knowledge assessment used a questionnaire. Results: Most of the respondents' aged group ≤14 were 11 respondents (37.9%), 17 respondents with junior high school education category (58.6%), followed 10 respondents by high school / vocational education level (34.5%), then 2 respondents from College level (6.9%) Respondents got the information about Covid-19 through the internet 17 respondents (58.6%) As many as 24 respondents have a good level of knowledge about Covid-19 (82.8%), and as many as 5 respondents with a sufficient category (17.2%) Conclusions: The level of PAYD students knowledge about Covid-19 is dominated by good categories.